2000
DOI: 10.1046/j.1365-313x.2000.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone treatment rapidly activates MAP kinase signalling in plants

Abstract: ). ² These two authors contributed equally to the work described here. SummaryBrief exposure to ozone, a potent cross-inducer of plant stress responses, leads within minutes to activation of an ERK-type MAP kinase (approximately 46 kDa) in tobacco. This activation process is calcium-dependent and can be blocked both by free radical quenchers and by a speci®c inhibitor of MEK-1 (MAPKK). Hydrogen peroxide and superoxide anion radicals can substitute for ozone as the activation stimulus, which does not appear to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
175
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 65 publications
11
175
0
Order By: Relevance
“…Like MPK3 and MPK6 in Arabidopsis, the putative tobacco orthologs SIPK and WIPK also become activated by ozone and nitric oxide (Kumar and Klessig, 2000;Samuel et al, 2000). Paradoxically, overexpression as well as suppression of SIPK renders plants hypersensitive to ozone treatment (Samuel and Ellis, 2002).…”
Section: Ros and Abiotic Stresses Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…Like MPK3 and MPK6 in Arabidopsis, the putative tobacco orthologs SIPK and WIPK also become activated by ozone and nitric oxide (Kumar and Klessig, 2000;Samuel et al, 2000). Paradoxically, overexpression as well as suppression of SIPK renders plants hypersensitive to ozone treatment (Samuel and Ellis, 2002).…”
Section: Ros and Abiotic Stresses Ozonementioning
confidence: 99%
“…Paradoxically, overexpression as well as suppression of SIPK renders plants hypersensitive to ozone treatment (Samuel and Ellis, 2002). Overlapping but not completely interchangeable actions are known for SIPK and WIPK; WIPK activation usually is accompanied by SIPK activation, but some oxidative stresses preferentially activate SIPK and leave WIPK unaffected (Kumar and Klessig, 2000;Samuel et al, 2000). Plants overexpressing wildtype or constitutively active versions of SIPKK, a SIPKinteracting MAPKK (Liu et al, 2000), exhibit enhanced ozone resistance (Miles et al, 2005), whereas NtMPK4-silenced plants are hypersensitive to ozone (see above).…”
Section: Ros and Abiotic Stresses Ozonementioning
confidence: 99%
“…Moreover, cycloheximide treatment repressed the basal mRNA level of grx but not those of sodCc1 and trxh, indicating that protein synthesis is required for maintaining the basal level of grx expression under an unstressed condition. It has been shown that a MAP kinase cascade is involved in the signaling of oxidative stress in Arabidopsis (Arabidopsis thaliana) and tobacco (Nicotiana tabacum; Kovtun et al, 2000;Samuel et al, 2000). Hydrogen peroxide, superoxide, and ozone treatments activate a MAP kinase cascade, which is thought to regulate downstream stressresponsive genes.…”
Section: Association Of Map Kinase Cascade To Core-mediated Gene Regumentioning
confidence: 99%
“…Higher plants are also thought to adapt to oxidative stress through coordinate regulation of a battery of antioxidant genes. Although some cis-elements responsive to ROS (ocs element, Chen and Singh, 1999; as-1 element, Garreton et al, 2002) and mitogenactivated protein (MAP) kinase cascades that are activated by oxidative stress (Kovtun et al, 2000;Samuel et al, 2000) have been characterized in higher plants, the details of the regulatory mechanisms of the antioxidant defense system are still unclear. So far, no redox regulatory system of antioxidant genes in higher plants has been reported.…”
mentioning
confidence: 99%
“…H 2 O 2 induces the expression of defense-related genes such as GST, encoding glutathione S-transferase, and PAL, encoding Phe ammonia lyase (Levine et al, 1994;Desikan et al, 1998a;Grant et al, 2000). H 2 O 2 also activates mitogen-activated protein kinases (MAPKs), conserved signaling kinases that modulate gene expression and transduce cellular responses to extracellular stimuli Grant et al, 2000;Kovtun et al, 2000;Samuel et al, 2000). Furthermore, several studies indicate that H 2 O 2 is a key factor mediating programmed cell death (PCD) in response to pathogens, elicitors, and hormones (Tenhaken et al, 1995;Levine et al, 1996;Desikan et al, 1998a;Mittler et al, 1999;Solomon et al, 1999;Bethke and Jones, 2001).…”
mentioning
confidence: 99%